Time is money: Could deferred graduate retirement finance higher education? - Bilal Barakat (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2011)
Higher education is never free - the question is: who should pay for it? Current policy debates in Europe are increasingly focusing on raising the share of private funding. To date, policy discussions have centred on a relatively small number of alternatives, namely full public funding, tuition fees, either up-front or delayed and income-contingent, or a surtax on graduate incomes. Here, I present an alternative that, to my knowledge, has not been suggested previously, but sidesteps some important objections against other forms of private contributions. The basic idea explored here is to increase the statutory retirement age for higher education graduates relative to non-graduates. In principle, the resulting decrease in future public pension liabilities can be converted into increased funds for present spending on higher education. In this first discussion of the above proposal I consider important caveats, perform an order-of-magnitude estimate of financial feasibility, i.e. whether deferred graduate retirement (DGR) could potentially raise sufficient funds to replace tuition fees, and discuss advantages and disadvantages compared to more established policy options. I conclude that, at least in the European context, DGR is potentially feasible both financially and politically, has a number of desirable properties compared to the alternatives, and deserves more serious investigation.
Keywords: 330; Higher education; cost-sharing; retirement age; Flexible Altersgrenze; Akademiker; Hochschulfinanzierung; Verteilungswirkung; Studierende; Österreich